ANALISIS PEMASUKAN DANA PIHAK KETIGA DAN PENYALURAN KREDIT DIMASA COVID-19 PT. BANK TABUNGAN NEGARA CABANG KENDARI - Desak Made Ayu Ulfasari; Muh. Nur; Safaruddin (STIE ENAM ENAM KENDARI, 2022)
The purpose of this research is to find out and analyze the income of TPF and credit distribution during the Covid-19 period at Bank BTN Kendari Branch. The object of this research is TPF Income and Credit Distribution during the Covid-19 Period at PT. Bank BTN Kendari Branch.The time of the study was carried out from April to June 2021. The results of the study show that: 1) Trends in the development of TPF (third party funds) at PT. The State Savings Bank Kendari Branch has increased from year to year with an average of Rp. 116,090,000,000 with an average growth of 13.46% per year. The development of TPF (third party funds) The development of TPF (third party funds) is due to an increase in demand deposits which each year increases in 2016-2020 and also increases in deposits and savings each year, 2) The trend of development of credit distribution at PT. The State Savings Bank Kendari Branch has increased from year to year with an average of Rp. 249,400,000,000 with an average growth of 14.41 percent per year. Credit distribution at the Kendari Branch of the State Savings Bank has increased due to the increase in DPK income each year. The higher the DPK income, the better or better the distribution of credit.